MATOS ADDITION EFFECT ON SOIL CLAY CBR VALUE MIXED WITH RICE HUSK ASH VIEWED FROM SOAKED TIME - Duha, Mayunata; Iswan, Iswan; Purwadi, Ofik Taufik (Jurnal Rekayasa Sipil dan Desain, 2018)
Clay is a type of soil that has high water content and generally has a low soil carrying capacity.  This can cause problems when the soil will be built a construction on it.  Clay will easily saturated when the rainy season comes so that the soil water content therein increases which makes its carrying capacity decreased.  The addition of matos and rice husk ash is one of the methods to stabilize the soil.  With this method, this research is expected to know the effect of the addition of these substances in saturation condition by reviewing the research samples on the value of CBR immersion. This research was conducted at the Laboratory of Soil Mechanics Faculty of Engineering, University of Lampung by making optimum sample which has the highest CBR value then searched the effect of adding the duration of immersion in 7, 14, 21, and 28 days.  The soil samples taken from Sidorejo village, Sidomulyo subdistrict, South Lampung are clay soil which has the original soil CBR value of 7.3% and 31.8% in the CBR optimum curing soil mixture.The soil stabilization method experienced by the sample showed a decrease of CBR value from 15.5% on the duration of the immersion time of 7 days to 8% in the duration of the 28 day immersion time.  This decreased immersion CBR value indicates that the addition of the duration of the immersion time resulted in the CBR value of the soil mixed soil samples decreasing as the soaking time of the soil samples grew. Keywords : Matos, immersion CBR, Rice Husk Ash, Clay.